Channelling the Unknown: Noise in Art Ecosystems - Paul Goodfellow (Arts, 2022)
At both the individual and societal levels, we are entangled within environmental, social, and technological systems that shape our material and emotional states. Contemporary art needs to integrate and challenge the information circulating within these interacting systems to address our increasingly complex lifeworld. This systemic understanding emerged in the 1960s as part of a broader growth in relational thinking within the natural and social sciences, which extended the conceptual boundaries of the artwork. The ecosystem, a model originally developed within ecology, is an example of a systems model as it describes the flow of matter, energy, and information through the physical world. This model has evolved into a powerful analogical tool to describe contemporary culture’s entanglement with nature and technology. The ecosystem model is invoked here to describe how information flows through the artwork. The paper suggests that art is a vital form of communication as it can channel noise or unknown information. This channelling is demonstrated with the artwork, The Creation Myth (1998), by Jason Rhoades. This work anticipated the convergence of natural and technological systems, and it demonstrates the ability of the arts to channel unknown messages or noise, thereby disrupting the dominant signals of contemporary culture.